Marketing Strategy for Layer Chicken Breeds in the Development of Micro Enterprises as a Means of Entrepreneurship Education (Case Study: Garuda Farm Layer Chicken Business) - Fatika, Inda; Yusrianto Sholeh (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze the marketing strategy of laying hens in the development of micro-enterprises, with a case study at Garuda Farm in Ombul Village, Arosbaya District, Bangkalan Regency. A descriptive qualitative method was employed, using data collection techniques such as interviews, observations, and documentation. The findings reveal that Garuda Farm applies a direct marketing strategy by building personal relationships with local consumers. The success of this strategy is influenced by key factors including consistent product quality, friendly customer service, and the provision of high-quality feed to maintain poultry health and productivity. Additionally, the active involvement of the owner in operational activities strengthens the effectiveness of marketing efforts. The study concludes that direct marketing strategies significantly contribute to the development of rural micro-enterprises and offer potential for future market expansion through digital innovation.